2021
DOI: 10.1093/advances/nmaa104
|View full text |Cite
|
Sign up to set email alerts
|

Roles of the Polyphenol–Gut Microbiota Interaction in Alleviating Colitis and Preventing Colitis-Associated Colorectal Cancer

Abstract: Accumulating evidence indicates that the gut microbiota can promote or inhibit colonic inflammation and carcinogenesis. Promotion of beneficial gut bacteria is considered a promising strategy to alleviate colonic diseases including colitis and colorectal cancer. Interestingly, dietary polyphenols, which have been shown to attenuate colitis and inhibit colorectal cancer in animal models and some human studies, appear to reach relatively high concentrations in the large intestine and to interact with the gut mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
69
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(73 citation statements)
references
References 193 publications
4
69
0
Order By: Relevance
“…This suggests that there is a special connection between probiotics and CRC. In fact, numerous studies have demonstrated the anti-tumor effects of probiotics such as L. acidophilus, L. casei, L. plantarum, and B. longum (13,14). However, before a specific probiotic strain can be considered part of a cancer treatment regimen, its function needs to be assessed in detail (15).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that there is a special connection between probiotics and CRC. In fact, numerous studies have demonstrated the anti-tumor effects of probiotics such as L. acidophilus, L. casei, L. plantarum, and B. longum (13,14). However, before a specific probiotic strain can be considered part of a cancer treatment regimen, its function needs to be assessed in detail (15).…”
Section: Discussionmentioning
confidence: 99%
“…Many current studies have shown that the intestinal flora plays an important role in the formation of the inflammatory microenvironment and the promotion of tumor growth ( Brennan and Garrett, 2016 ). The gut microbiota of CAC mice is characterized by reduced microbial diversity and reduced abundance of probiotics (including Bacteroides, Lactobacillus ) ( Zhao and Jiang, 2020 ), and Alloprevotella ( Wei et al., 2018 ), and the expansion of pathogenic bacteria, such as Proteobacteria ( Shin et al., 2015 ; Litvak et al., 2017 ), Muribaculaceae ( Pereira et al., 2020 ), Akkermansia ( Ijssennagger et al., 2015 ), Klebsiella ( Olm et al., 2019 ), and Citrobacter ( Collins et al., 2014 ). Gut microbiome dysbiosis leads to changes in cytokine activity, inflammatory signaling pathway activation (e.g., TLR4, TLR5, NF-κB, and MAPKs), and intestinal barrier function weakening, all of which provide a pro-inflammatory microenvironment for tumor promotion ( Fukata et al., 2009 ; Choi et al., 2013 ; Waldner and Neurath, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…These components may help to improve the structure of the intestinal flora. Many studies have shown that polyphenols can decrease proinflammatory microbes and counteract disease‐induced dysbiosis in colitis models (Zhao & Jiang, 2021 ). Moreover, the bioactive phenol is considered to be the main component of Pu‐erh tea responsible for its health‐promoting function (Etxeberria et al., 2013 ).…”
Section: Discussionmentioning
confidence: 99%